Resilience and coping strategies coping strategies in primary school teachers - Magdalena Boczkowska (Studia z Teorii Wychowania)
The aim of the study was to assess the coping strategies used in the context of resilience among elementary school teachers. A cross-sectional survey was conducted with 197 elementary school teachers. To assess coping strategies, the COPE questionnaire in the Polish adaptation of S. Piatek and K. Wrześniewski. Resilience was measured using the Teachers' Resilience Scale (TRS) by M. Platsidou and A. Danilidou in a Polish adaptation by M. Boczkowska. The study showed that resilience statistically significantly differentiates the applied stress coping strategies among elementary school teachers, but only in terms of the strategies "Focus on the problem" and "Denial". The results allow us to conclude that elementary school teachers demonstrating high levels of resilience in the face of stressful events do not focus only on them, but rather activate other coping strategies that facilitate positive adaptation.